صورة أصحاب العاهات في متخيل الغرب الإسلامي - مقورة، سمية (جامعة الأمير عبد القادر للعلوم الإسلامية - كلية أصول الدين, 2021)
تتزاحم الصور المختلفة حول أصحاب العاهات والأمراض في متخيل الغرب الإسلامي، تمايزت بين السلبية والإيجابية؛ بين المدح والذم، كانت وراءها مرجعيات تاريخية غذتها على مرور قرون، وأخرى دينية ساهمت في تشكيلها، تلك الصور كانت لها انعكاساتها على المستوى المعيشي وحتى النفسي للمرضى. وقد حاولنا في هذا المقال ذكر مختلف تلك الصور النمطية المتمركزة في اللاوعي الجمعي حول هذه الفئة (مرضى: الجذام، البرص، الجرب، العرج، الجنون، فقدان البصر ...).
Different images crowd around people with disabilities and diseases in the imagination of the Islamic West, differentiated between negative and positive; between praise and slander, behind them were historical references that nourished them over the passage of centuries, and religious ones that contributed to their formation. These images had repercussions on the standard of living and even the psychological level of patients. In this article, we have tried to mention the various stereotypes centered in the collective unconscious about this category (patients: leprosy, leprosy, scabies, lameness, insanity, blindness...).
Keywords: المتخيل -- أصحاب العاهات -- ذوي الاحتياجات الخاصة -- الصورة النمطية -- الغرب الإسلامي